ENSURING ENVIRONMENTAL SAFETY OF ANIMAL ORIGIN BY STUDYING THE MECHANISM OF TRANSMISSION OF TULAREMIA IN THE NATURAL FOCAL ZONE OF STAVROPOL REGION - Sergey Aleksandrovich Emelyanov; Denis Yurievich Degtyarev (Современная наука и инновации)
Based on the analysis of the results of many years of study of the epizootic situation in the natural focal zone of tularemia in the Stavropol region and study of pathogens transmission mechanism zoonosis of wild animals in the intensity of the epidemic process is given a forecast and assessment of epidemiological risks, identify efective measures to combat this disease to ensure the biological safety of production products of animal origin in the conditions of modern agriculture.